(untitled) (Education in the 21st Century, 2022)
In the article entitled "Features of the application of the modern method of teaching quatrains," we tried to show the features of the application of the method related to the nature of the material being taught and the originality of the writer’s imaginative system. The originality of the application of this method became visible on the basis of the analysis of the story of A. K. Bakuntsa "White horse". The purpose of the article is to reveal the essence of the above mentioned method through interesting observations, to identify the principles of teaching the material by this method, indicating and justifying the advantages due to the relevant features of this method of teaching and to point out the features arising from the purpose of teaching. The novelty of the research is the observation of the features of the application of the modern method of four-volume training. According to the above method, the images in the artwork were analyzed, their philosophical and psychological layers were emphasized. The relevance of the research is due to the requirements of modern teaching methodology to consider the process of teaching literary works, making it consonant with modern educational programs. In the article, using the verse method we showed the effectiveness of modern teaching methods, and with their help, the possibilities of a more meaningful analysis of the work of art. For the first time, the study of Ak. Bakunet`s story "White Horse" was considered with an emphasis on the specifics of the author’s heyday. As a result of the research, we came to the following conclusions: the use of the method contributes to a deeper analysis of the taught material, a multi-level and comprehensive knowledge of the material by students, a large-scale presentation of a work of art, the creation of a more interesting and meaningful lesson. Keywords and phrases: consultation, eloquence, ideological problems, means of imagery, philosophy.